1990
DOI: 10.1007/bf01074098
|View full text |Cite
|
Sign up to set email alerts
|

Changes in religious beliefs, attitudes, and practices following near-death experiences: An Australian study

Abstract: This study examined changes in religious beliefs, attitudes, and practices in the lives of 50 near-death experiencers. I attempted to clarify whether these changes were to greater religiousness or to a deeper spirituality. I found that before the near-death experience (NDE), my respondents were no more religious or spiritually inclined than the general Australian population. Following the NDE there was a statistically significant shift towards spiritu ality on most items investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 8 publications
5
35
0
Order By: Relevance
“…In support of this, research has indicated a concomitant increase in afterlife beliefs amongst NDErs (Flynn, 1986;Grey, 1985;Greyson & Stevenson, 1980;Ring, 1980;Sabom, 1982;Sutherland, 1990). van Lommel et al (2001) discovered NDErs were likely to report a new or strengthened belief in the afterlife, in comparison to the non-NDE control group (who also came close to death).…”
Section: Loss Of the Fear Of Deathmentioning
confidence: 81%
See 3 more Smart Citations
“…In support of this, research has indicated a concomitant increase in afterlife beliefs amongst NDErs (Flynn, 1986;Grey, 1985;Greyson & Stevenson, 1980;Ring, 1980;Sabom, 1982;Sutherland, 1990). van Lommel et al (2001) discovered NDErs were likely to report a new or strengthened belief in the afterlife, in comparison to the non-NDE control group (who also came close to death).…”
Section: Loss Of the Fear Of Deathmentioning
confidence: 81%
“…Furthermore, this loss of the fear of death appears to be maintained over time (Sabom, 1982;Sutherland, 1990;van Lommel et al, 2001). In their seminal longitudinal study of NDEs in cardiac arrest survivors, van Lommel et al (2001) found the majority of the 62 patients reporting an NDE after cardiac arrest, and who were interviewed shortly after the experience, did not indicate any fear of death.…”
Section: Loss Of the Fear Of Deathmentioning
confidence: 94%
See 2 more Smart Citations
“…However, prior religious belief or knowledge of NDEs is not correlated with having an NDE 12,14,15,17 , although cultural and religious factors may influence the interpretation of the experience 28 . Regarding this issue, NDErs show significant belief in life after death following their NDE that they did not have before the experience 10,15,25,29 . Also, children, who are presumably less culturally conditioned with fewer expectations about death, describe NDEs that are similar to adults' descriptions 30 .…”
Section: Psychological Theoriesmentioning
confidence: 99%